2010
DOI: 10.1002/ange.200905513
|View full text |Cite
|
Sign up to set email alerts
|

Reaktions‐Diffusions‐Systeme für intrazellulären Transport und Kontrolle

Abstract: Chemische Reaktionen können Zellen nur am Leben erhalten, wenn die beteiligten Verbindungen an den erforderlichen Stellen zeitlich präzise angeliefert werden. Die meisten Forschungen haben sich bislang auf aktive Transportmechanismen konzentriert, obwohl die passive Diffusion oft gleich schnell ist und weniger Energie erfordert. Um die Vorteile dieser Transportform zu nutzen, haben die Zellen ausgeklügelte Reaktions‐Diffusions(RD)‐Systeme entwickelt, die zahlreiche zelluläre Funktionen kontrollieren – von Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 306 publications
(367 reference statements)
0
11
0
Order By: Relevance
“…Signal transport through tissues can also be treated, approximately, as a diffusion process by combining membrane permeation with permeability P and bulk diffusion with diffusion coefficient D into an effective diffusion coefficient D eff =[( PL cell ) −1 + D −1 ] −1 , in which L cell is the size of the cells . For a very nice introduction into reaction–diffusion phenomena the reader is also referred to the review by Soh et al …”
Section: Communication Between Artificial Cellsmentioning
confidence: 99%
“…Signal transport through tissues can also be treated, approximately, as a diffusion process by combining membrane permeation with permeability P and bulk diffusion with diffusion coefficient D into an effective diffusion coefficient D eff =[( PL cell ) −1 + D −1 ] −1 , in which L cell is the size of the cells . For a very nice introduction into reaction–diffusion phenomena the reader is also referred to the review by Soh et al …”
Section: Communication Between Artificial Cellsmentioning
confidence: 99%
“…The RD equations were solved numerically using the Crank–Nicolson algorithm15d, 21 with the initial conditions (time t =0) inside the MOF given by [PB] 0 =0 M , [S*] 0 =0.79 M ,22 and [PB⋅S] 0 =0 M , and the boundary condition setting the PB concentration outside of the MOF crystal as constant, [PB]=10 −7 M (since the number of molecules in solution is thousands of times higher than the maximum number of PB molecules adsorbed into the crystal). The RD equations were solved for different trial values of the D PB and K eq parameters, the optimal values of which were then found by minimizing the quadratic error between the experimental and modeled concentration profiles; this procedure was performed according to the Nelder–Mead simplex algorithm 15…”
mentioning
confidence: 99%
“…Self‐organization outside the thermodynamic equilibrium is important in the context of life,1, 2 and has inspired development of artificial dynamic materials and systems3, 4 on scales from molecular,59 through nanoscopic1012 and microscopic,13, 14 to macroscopic 15. 16 One of the singular features of non‐equilibrium self‐organization in cells or organisms is their ability to couple several subsystems into larger, dynamic machinery 2. In man‐made ensembles, such synthetic ability is largely lacking, though there are some interesting examples where molecular‐scale, non‐equilibrium systems such as chemical oscillators control dimensions/contractility of gels or polymers17, 18 or periodically shift complexation or precipitation equilibria 1922.…”
mentioning
confidence: 99%